Teacher Learning Process in Implementing the Independent Learning Curriculum in the High School Environment - Wijayanto, Pikir Wisnu; Ariefianto, Lutfi; Judijanto, Loso (Universitas Pendidikan Ganesha, 2024)
Teachers in the Independent Curriculum have a vital role, starting from planning learning, compiling materials, choosing models, implementation methods, and assessment. However, the fact is that out of 70 students, 34 people had a mean score of 28.26. Another point is that 68.65% did not match the assignment and 48% of students did not complete it. It is urgent to research because there are differences in theory, expectations, and reality in the field. The aim of this study is to analyze management prepares learning implementation plans and implementing the independent curriculum at high school. The research method used is mixed research. The population is high school students with a sample of 156 people consisting of 130 students and 26 teachers—data collection techniques using surveys and interviews. Instruments are arranged based on indicators and shared via Google from the link. The data analysis technique uses SPSS Statistics 26.0 while the interview data is analyzed by data collection, reduction, and concluding. The results and findings show that 22% of teachers prepared learning implementation plans, 23.67% of teachers were able to deliver the material, 32.49% were able to assess objectively, 26.76% of students experienced changes in behavior from learning and only 34.26% of teachers were able to assess objectively carry out learning evaluations of the independent learning curriculum. The interview results intersect with the survey results. In conclusion, the implementation of the independent learning curriculum needs to be evaluated and there needs to be training.